Antimicrobial Susceptibility and Resistance Genes in Streptococcus uberis Isolated from Bovine Mastitis in the Czech Republic - Monika Zouharova; Katerina Nedbalcova; Katarina Matiaskova; Petr Slama; Jan Matiasovic (MDPI AG, 2023)
Streptococcus uberis is one of the most important causative agents of mastitis and is a common reason for the use of antimicrobials in dairy cows. In this study, we assessed the antimicrobial susceptibility of 667 S. uberis isolates originating from 216 Czech dairy farms collected between 2019 and 2023 using the broth microdilution method. We tested 140 of the isolates for the presence of antimicrobial genes using whole-genome sequencing and evaluated their relationship with phenotypic resistance. Streptococcus uberis isolates showed high levels of resistance to tetracycline (59%), followed by streptomycin (38%) and clindamycin (29%). Although all of the isolates were susceptible to beta-lactams, a relatively high percentage of intermediately susceptible isolates was recorded for ampicillin (44%) and penicillin (18%). The isolates were mainly resistant to tetracycline alone (31.3%); the second most frequent occurrence of the phenotypic profile was simultaneous resistance to tetracycline, streptomycin, and clindamycin (16.6%). The occurrence of antibiotic resistance genes did not always match the phenotypic results; in total, 36.8% of isolates that possessed the ant(6)-Ia gene did not show phenotypic resistance to streptomycin. To a lesser extent, silent genes were also detected in clindamycin and tetracycline. This study confirmed the high susceptibility of S. uberis to penicillins used as first-line antimicrobials for S. uberis mastitis treatment.